2014
DOI: 10.1302/0301-620x.96b11.33617
|View full text |Cite
|
Sign up to set email alerts
|

The outcome at ten years of lateral closing-wedge high tibial osteotomy

Abstract: The aim of this study was to examine the functional outcome at ten years following lateral closing wedge high tibial osteotomy for medial compartment osteoarthritis of the knee and to define pre-operative predictors of survival and determinants of functional outcome. 164 consecutive patients underwent high tibial osteotomy between 2000 and 2002. A total of 100 patients (100 knees) met the inclusion criteria and 95 were available for review at ten years. Data were collected prospectively and included patient de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 32 publications
2
54
1
1
Order By: Relevance
“…In conclusion, in the ex vivo setting, SHO was associated with significant alterations in thoracic limb alignment when assessed using both standing and recumbent limb positions. The results of our study suggest a novel mechanism by which SHO might assert clinical effects in vivo, namely through alteration of thoracic limb alignment as has been documented in high tibial osteotomies in people . Future work is necessary to determine whether the differences in limb alignment described in our ex vivo study occur after SHO in the clinical setting.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In conclusion, in the ex vivo setting, SHO was associated with significant alterations in thoracic limb alignment when assessed using both standing and recumbent limb positions. The results of our study suggest a novel mechanism by which SHO might assert clinical effects in vivo, namely through alteration of thoracic limb alignment as has been documented in high tibial osteotomies in people . Future work is necessary to determine whether the differences in limb alignment described in our ex vivo study occur after SHO in the clinical setting.…”
Section: Discussionmentioning
confidence: 61%
“…The results of our study suggest a novel mechanism by which SHO might assert clinical effects in vivo, namely through alteration of thoracic limb alignment as has been documented in high tibial osteotomies in people. 9,10,38,39 Future work is necessary to determine whether the differences in limb alignment described in our ex vivo study occur after SHO in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“… 19 2015 OCS 89 6 5 Hernigou and Ma 20 2001 OCS 245 8 5, 10 Howells et al . 21 2014 OCS 95 5 5, 10 Hui et al . 22 2010 OCS 413 6 5, 10 Koshino et al .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that a pre-operative BMI higher than 27.5 is a significant risk factor for early failure [25], and patients with BMI over 30 exhibit significantly lower KSS and WOMAC scores 5 years after HTO [28]. Moreover, HTO is not advisable for patients older than 65 years due to the 7.6% increased risk per year of age and the 1.5-fold relative risk of failure compared to younger patients [29].…”
Section: Discussionmentioning
confidence: 99%